Connections between competencies and abilities in female artistic gymnasts and handball players - Wehovszky, V.; Nagykáldi, C.; Kalmár, Z.; Ökrös, C. (Frontiers in Sports and Active Living, 2025)
Competencies play a pivotal role in addressing challenges in various domains of life, including physical education and sports, where their complexity and diversity are particularly emphasized. The primary aim of this study is to explore the development of sport-specific competencies from the perspective of physical abilities. A secondary aim is to investigate potential differences in competency profiles of different sports disciplines. To this end, the following hypotheses were proposed: Fundamental physical abilities are hypothesized to serve as prerequisites for the development of competencies. It is expected that these physical abilities will exhibit strong correlations with competencies understood as acquired skills. It is further hypothesized that there are measurable differences in competencies understood as associated with physical abilities among athletes from different sports, specifically between female gymnasts and handball players in our sample. Physical abilities were assessed through self-perception using a Likert scale, not through objective performance tests. To test these hypotheses, questionnaire-based assessments were employed. Physical abilities were measured by using the Actual Fit Efficacy (AFE) test, which evaluates ten distinct physical attributes. Validity was demonstrated through a correlation of R = 0.78 with the physical factor of the Competitor Self-Assessment Method (CSAM) meeting standard validity criteria. Competencies were assessed by using the CSAM, which includes 12 Likert-type scales. A test-retest analysis revealed high correlation coefficients for all scales (p < 0.001), confirming reliability. Criterion validity was established through comparisons of performance under low- and high-achievement conditions, with significantly higher scores observed during high-performance scenarios (p-values ranging from <0.05 to <0.001).